Comparing Topical Vancomycin Vs Control Procedure Focus On Staphylococcus Event In Spinal Surgery Procedures: A Systematic Review And Meta-Analysis - Puspawan, Ni Putu Eka Gloria (Indonesian Journal of Multidisciplinary Science, 2025)
OBJECTIVE: This study aimed to evaluate the effectiveness of topical vancomycin powder versus standard prophylaxis in preventing gram-positive bacterial infections, specifically Streptococcus species, in spinal surgery patients through systematic review and meta-analysis. DATA SOURCES: A comprehensive search was conducted across PubMed, Cochrane Library, Scopus, and ScienceDirect databases. The search strategy incorporated "Spine Surgery," "Topical Vancomycin," "Surgical Site Infection," "Gram-positive," and "Staphylococcus." STUDY ELIGIBILITY CRITERIA: Studies were included if they involved adult patients undergoing spinal surgery, evaluated topical vancomycin powder applied directly to surgical wounds before closure, compared to control groups receiving standard systemic antibiotic prophylaxis alone, and reported surgical site infection rates with focus on gram-positive organisms. METHODS: Reviewers independently identified studies, extracted data, and assessed study quality using the Newcastle-Ottawa Scale. Risk ratios with 95% confidence intervals were calculated. Statistical heterogeneity was assessed using the I² statistic. RESULTS: Nine comparative studies involving 9,745 patients were analyzed. Streptococcus infections occurred in 44/3,943 (1.11%) in the vancomycin group versus 115/5,802 (1.98%) in the control group (risk ratio, 0.49; 95% confidence interval, 0.34-0.70; I², 4%). CONCLUSION: Topical vancomycin powder significantly reduced Streptococcus infections by 51% in spinal surgery patients, demonstrating consistent protective effects against gram-positive pathogens with minimal heterogeneity across studies.